2010
DOI: 10.1038/nm.2216
|View full text |Cite
|
Sign up to set email alerts
|

A dominant-negative mutation in the TRESK potassium channel is linked to familial migraine with aura

Abstract: Migraine with aura is a common, debilitating, recurrent headache disorder associated with transient and reversible focal neurological symptoms. A role has been suggested for the two-pore domain (K2P) potassium channel, TWIK-related spinal cord potassium channel (TRESK, encoded by KCNK18), in pain pathways and general anaesthesia. We therefore examined whether TRESK is involved in migraine by screening the KCNK18 gene in subjects diagnosed with migraine. Here we report a frameshift mutation, F139WfsX24, which s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

16
312
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 320 publications
(329 citation statements)
references
References 29 publications
16
312
1
Order By: Relevance
“…two-pore domain potassium channel (K2P), encoded by KCNK18, was recently reported (Lafreniere et al 2010).…”
Section: Migraine and Familial Hemiplegic Migraine (Fhm)mentioning
confidence: 99%
See 1 more Smart Citation
“…two-pore domain potassium channel (K2P), encoded by KCNK18, was recently reported (Lafreniere et al 2010).…”
Section: Migraine and Familial Hemiplegic Migraine (Fhm)mentioning
confidence: 99%
“…By screening the KCNK18 gene in a large multigenerational family with typical migraine with aura, inherited in a dominant fashion, Lafreniere et al (2010) identified a mutation in TRESK (F139WfsX24). They also identified prominent TRESK expression in migraine salient areas such as the trigeminal ganglion.…”
Section: Migraine and Familial Hemiplegic Migraine (Fhm)mentioning
confidence: 99%
“…Some mutations that were found to be related with hemiplegic migraine (de Vries et al, 2006(de Vries et al, , 2009, and common migraine (Lafrenière et al, 2010), are good examples of mutation biomarkers. Some polymorphisms were also found to be more valuable for screening patients with higher susceptibility into migraine attack in the future (De Vries et al, 2006).…”
Section: Genetic Biomarkersmentioning
confidence: 99%
“…Like other complex genetic traits, finding responsible genes are much more difficult (de Vries et al, 2006). Despite these problems and absence of any evidence of association between genes encoding the ion channels and common migraine in previous studies (Nyholt et al, 2008), it has been reported recently that there is a strong genetic link to common forms of migraine (Lafrenière et al, 2010). Using a candidate gene approach and functional analysis, researchers have identified a mutation, F139wfsX24, in the gene encoding the two-pore domain potassium channel TRESK (TWIK-related spinal cord potassium channel) KCNK18 in the patients with migraine with aura.…”
Section: Common Migrainementioning
confidence: 99%
See 1 more Smart Citation